High Tide at Gettysburg : The Campaign in Pennsylvania - Tucker, Glenn (Indianapolis, New York The Bobbs-Merrill Company, Inc., 1958)
Reviews the strategies and the importance of the Civil War battle at Gettysburg in 1863 and the battle's importance in the course of the war--Publishers weekly.
Include Maps, Notes, Bibliography and Index.
The Campaign in Pennsylvania
Keywords: Gettysburg Campaign (1863) -- Pennsylvania--Gettysburg -- Gettysburg, Battle of (Pennsylvania : 1863) -- United States -- American Civil War (1861-1865) -- Military campaigns -- Pennsylvania